2011
DOI: 10.1097/fjc.0b013e318224e0a2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Levosimendan in Patients With Acute Heart Failure

Abstract: Heart failure is a major public health problem because of its high prevalence and impact on mortality, morbidity, quality of life, and social costs. The aim of this analysis was to estimate the effects of the novel inodilator levosimendan versus standard inotropic therapy (ST) of dobutamine in acute heart failure. A study population of 292 patients with acute heart failure was derived from an observational registry of patients referred to our department. Of these, 147 patients received iv levosimendan (0.05-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…As far as comparison is possible, such outcomes appear to be in line with those which are reported in published clinical trials of levosimendan [15][16][17][18][19] and in a comprehensive meta-analysis [14], in particular with regards to shortened LOS; the gain of 1.5 days reported by Fedele et al [21] is the same as that reported by Landoni et al [14]. In other words, all these clinical findings appear to be confirmed by a "real-life" clinical experience in Italy.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As far as comparison is possible, such outcomes appear to be in line with those which are reported in published clinical trials of levosimendan [15][16][17][18][19] and in a comprehensive meta-analysis [14], in particular with regards to shortened LOS; the gain of 1.5 days reported by Fedele et al [21] is the same as that reported by Landoni et al [14]. In other words, all these clinical findings appear to be confirmed by a "real-life" clinical experience in Italy.…”
Section: Discussionsupporting
confidence: 85%
“…in the reference study [21]). Such amount is defined in the model below (savings from rehospitalization rate reduction due to…”
Section: Savings From a Reduction In Rehospitalization Ratementioning
confidence: 89%
See 3 more Smart Citations